Contemporary non-statin therapies for dyslipidemia management: achieving current lipid targets - Carlos I. Ponte-Negretti; Alberto Lorenzatti; Fernando Wyss-Quintana; Rodrigo Alonso; Máxima Méndez-Castillo; Osiris Valdez-Tiburcio; Vladimir E. Ullauri-Solórzano; Camila Y. Ullauri-Valcárcel; Adriana Puente-Barragán; Luz C. Zárate-Correa; José G. Prieto-Marín; Isaac A. Suárez Sangucho; et al. (Frontiers in Medicine, 2026)
The current treatment of dyslipidemia in patients with cardiovascular risk (CR) is based on three well-defined principles: First, given the extensive evidence demonstrating the association between elevated low-density lipoprotein cholesterol (LDL-C) levels and cardiovascular risk, the primary therapeutic target is LDL-C. Second, as current guidelines recommend LDL-C targets below 55 mg/dL for high-risk patients, therapeutic goals according to risk level should be achieved as early as possible, and combination therapy is increasingly necessary. Third evidence indicates that non-statin therapies—including ezetimibe, bempedoic acid, PCSK9 inhibitors (evolocumab and alirocumab), and inclisiran—provide substantial LDL-C reductions and reduce cardiovascular events. These agents are particularly effective in very high-risk and statin-intolerant populations, with bempedoic acid addressing both lipid and inflammatory pathways. Additionally, the fixed-dose combination of bempedoic acid and ezetimibe produces an approximately 36.2% reduction in LDL-C in high-risk patients. Risk-stratified guidelines recommend ezetimibe as first-line add-on therapy, followed by PCSK9 inhibitors or bempedoic acid based on residual LDL-C levels and tolerability. Alirocumab has demonstrated a significant reduction in the primary composite endpoint of major adverse cardiovascular events (MACE), with a favorable trend in all-cause mortality. Furthermore, inflammation (measured by hsCRP) provides complementary prognostic information beyond LDL-C. This expert position paper proposes practical algorithms for a precision medicine approach in Latin America, matching treatment intensity to individual risk profiles for the primary and secondary prevention of atherosclerotic cardiovascular disease.